Three-dimensional echocardiography in congenital heart disease: an expert consensus document from the European Association of Cardiovascular Imaging and the American Society of Echocardiography. (21st September 2016) - Simpson, John; Lopez, Leo; Acar, Philippe; Friedberg, Mark; Khoo, Nee; Ko, Helen; Marek, Jan; Marx, Gerald; McGhie, Jackie; Meijboom, Folkert; Roberson, David; Van den Bosch, Annemien; et al.
Abstract: Three-dimensional echocardiography (3DE) has become important in the management of patients with congenital heart disease (CHD), particularly with pre-surgical planning, guidance of catheter intervention, and functional assessment of the heart. 3DE is increasingly used in children because of good acoustic windows and the non-invasive nature of the technique. The aim of this paper is to provide a review of the optimal application of 3DE in CHD including technical considerations, image orientation, application to different lesions, procedural guidance, and functional assessment.